NILAI NILAI RELIGIUS SELOKO ADAT PADA MASYARAKAT MELAYU JAMBI (TELAAH STRUKTURAL HERMENEUTIK) - Ade Rahima (Universitas Batanghari Jambi, 2014)
The objectives of this research to study the structure of traditional seloko of Jambi Malay as a means of education of religious valuesThis research used content analysis method to analyze the extrinsic elements of seloko containing religious values. This method was combined with structural hermeneutic study techniques to reveal the structure and implicit meanings of the texts in Jambi Malay seloko. Data in this research are traditional seloko containing religious values. Primary sources of data were obtained from a collection of traditional seloko of Jambi Malay recorded by a team of Lembaga Adat of Jambi Province, chaired by Hasip Kalimudin Sham (Pokok-pokok Adat Pucuk Jambi Sembilan Lurah: Hukum Adat Jambi, 2001) and (Pokok-pokok Adat Pucuk Jambi Sembilan Lurah: Sastra Adat Jambi, 2001). The results of this research show that the themes of traditional seloko of Jambi Malay community are related to the religious values of man’s relationship with God, man with nature, man with society, and man with himself.Key word: Religius, Values, Tradisional, Seloko.